2014
DOI: 10.1021/cm503405a
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Desulfurization of H2S: High Sorption Capacities by Mesoporous Cobalt Oxide via Increased H2S Diffusion

Abstract: Mesoporous cobalt oxides (M-Co-X, X = 150, 250, 350, 450°C) with tunable porosity and crystallinity were synthesized based on an inverse micelle soft template method. They are the members of recently discovered University of Connecticut (UCT) mesoporous materials. The M-Co-X materials were investigated as desulfurizing sorbents in a fixed bed reactor in the temperature range of 25−250°C. A considerably high sulfur sorption capacity was observed even at room temperature (13.4 g S/100 g sorbent), and very high v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…Since the surface area of Co 3 O 4 was undetermined, the low adsorption capacity was probably due to its low surface area. This inference was supported by the reported work of Pahalagedara et al The study reported mesoporous Co 3 O 4 with a surface area of 143 m 2 g −1 and an adsorption capacity of 134 mg g −1 at room temperature 14 . Wang and coworkers integrated Co 3 O 4 in three-dimensionally ordered macroporous silica for room temperature desulfurization process, where the adsorption capacity reached as high as 189 mg g −1 15 .…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Since the surface area of Co 3 O 4 was undetermined, the low adsorption capacity was probably due to its low surface area. This inference was supported by the reported work of Pahalagedara et al The study reported mesoporous Co 3 O 4 with a surface area of 143 m 2 g −1 and an adsorption capacity of 134 mg g −1 at room temperature 14 . Wang and coworkers integrated Co 3 O 4 in three-dimensionally ordered macroporous silica for room temperature desulfurization process, where the adsorption capacity reached as high as 189 mg g −1 15 .…”
Section: Introductionsupporting
confidence: 70%
“…Jun et al reported the formation of Co 9 S 8 after high-temperature oxidation of H 2 S over ZnCoTiO 4 54 . Pahalagedara et al reported the formation of Co 3 S 4 after the H 2 S desulfurization process over mesoporous Co 3 O 4 at 200 °C 14 . The PXRD pattern of spent NCO-D has sharp peaks in the entire 15°–70° range.…”
Section: Resultsmentioning
confidence: 99%
“…The final weight loss beyond 700˚C can be attributed to the evolution of lattice oxygen. 41 In contrast to that, CuAl MO 20%C catalyst shows evolution of surface oxygen starting at room temperature to 400˚C and lattice oxygen beyond 700˚C. These data along with the catalytic data obtained with and without catalyst and XRD studies before and after the reaction under air and nitrogen atmosphere ( Figure S8 and S10) collectively suggest that surface oxygen availability and facile reversibility of oxygen readsorption (Mars-van Krevelen mechanism) on the surface may account for the superior activity and high durability of the CuAl MO 20%C catalyst.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing of Co 3 O 4 to CoO leads to catalyst deactivation [6]. Considering the catalytic activity of showed that they act as effective sorbents for low temperature gas desulfurisation including conditions of excess of ammonia and water vapor [8,9,26]. Furthermore, their activity is superior even at room temperature.…”
Section: Electrical and Gas Sensor Propertiesmentioning
confidence: 99%
“…A very common interface used to alter gas sensing properties is a pn junction. N-type [4][5][6], and it is a promising material for water oxidation catalysts [7] and adsorbents for low temperature gas desulfurization [8,9]. The gas sensor properties of nanocrystalline materials based on cobalt-doped tin dioxide were previously investigated toward CO [10,11], H 2 [10][11][12][13][14], ozone [14] and acetone vapour [15].…”
Section: Introductionmentioning
confidence: 99%